2012
DOI: 10.1890/10-2036.1
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between small pelagic fish and young cod across the North Atlantic

Abstract: Species interactions that play out over large spatial scales are difficult to observe, particularly in the oceans. The current lack of empirical evidence for biologically meaningful interaction parameters likely delays the application of holistic management procedures. Here we estimate interactions during the early life history of fish across regions. We present separate and hierarchical Bayesian models that estimate the direction and strength of interactions between Atlantic cod and dominant pelagic fishes ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 78 publications
2
31
0
1
Order By: Relevance
“…The second was that, as predatory species recovered, the smaller, faster-growing species consumed juveniles of larger species, adding further fluctuations to community size structure recovery. An analogous effect can occur when prey can consume juvenile predators, as has been demonstrated for herring and cod (Walters & Kitchell 2001, Fauchald 2010, Minto & Worm 2012. In these cases, recovery of a prey species could delay recovery of its own predator, potentially enhancing the 'delayed predation' found here.…”
Section: Empirical Context and Model Assumptionssupporting
confidence: 55%
“…The second was that, as predatory species recovered, the smaller, faster-growing species consumed juveniles of larger species, adding further fluctuations to community size structure recovery. An analogous effect can occur when prey can consume juvenile predators, as has been demonstrated for herring and cod (Walters & Kitchell 2001, Fauchald 2010, Minto & Worm 2012. In these cases, recovery of a prey species could delay recovery of its own predator, potentially enhancing the 'delayed predation' found here.…”
Section: Empirical Context and Model Assumptionssupporting
confidence: 55%
“…This was potentially caused by extensive (over-) exploi tation of the stock, but several studies also indicate important changes in environmental factors potentially regulating the productivity (recruitment potential) of the North Sea cod stock. These include bottom-up, prey-driven changes ; changes in water temperature (Brander & Mohn 2004); and food web interactions (Kempf et al 2009, Minto & Worm 2012, Hjermann et al 2013. applied a principal component analysis to investigate the statistical relationship between cod recruitment strength and the abundance and species and size composition of dominant copepod species in the North Sea.…”
Section: Introductionmentioning
confidence: 99%
“…It is striking that the papers that suggest a substantial effect of herring predation on cod are based on modelling or statistical analyses (An dersen & Ursin 1977, Fauchald 2010, Speirs et al 2010, Minto & Worm 2012. In contrast, earlier work based on herring stomach samples (Daan et al 1985, Last 1989) concluded that herring predates on an insignificant amount of cod eggs.…”
Section: Discussionmentioning
confidence: 99%
“…The possible generality of such synergistic effects has been scrutinized by Ottersen et al (2013, this volume). A third mechanism may be that herring play a crucial role in limiting the recruitment of cod, through predation on, or competition with, cod eggs and larvae (Minto & Worm 2012). The predation mechanism has been discussed since the 1970s, as a period of exceptionally high recruitment years of cod and other gadoids (the 'gadoid outburst'), which started at approximately the same time that the stock of NS herring began to decline (Cushing 1980).…”
Section: Introductionmentioning
confidence: 99%